PENGARUH KOMPETENSI, SPI, MORALITAS DAN WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN KECURANGAN PENGELOLAAN DANA DESA - Ni Kadek Purnama Dewi; Sang Ayu Putu Arie Indraswarawati; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2022)
This survey aim to find of impact Competence of Village Officials, Internal Control System, Individual Morality and Whistleblowng System on Prevention of Fraud in Village Fund Managemen (Empirical Study in Villages in North Denpasar Subdistrict). The populationwere all 8 villages, amounting 142 persons. The study sample was decided use purposive sampling which is a certain criterion then the number of samples became 64 respondents. The data collection technique using questionnaires is then performed analysis multiple linier regression. From the yield of this survey, competence village officials, internal control system have not significant impact fraud prevention. But the morality individuals, whistleblowingi system have a positive impact fraud prevention.